PUSAT CLOTHING LINE BRAND LOKAL BANUA DI BANJARBARU DENGAN ARSITEKTUR EKSPRESIONIS - Alifi, Yuliana; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Banua Local Pride is a breakthrough for the local Banua brand clothing line community to get legal support and deserve to be the host when local fashion brands develop globally. The bazaar as a place for collaboration has not been able to become a place for developing BLP. The Banua Local Brand Clothing Line Center in Banjarbaru is an expressive identity space for the community and an interactive commercial center for local brands with the expression of their identity. The Clothing Line Center is a place for the community to recognize and appreciate the potential of Banua Local Pride. The design uses the Expressionist Architecture method using the concept of Expression-Identity through Expression-Enterprise, Community Based, and Locality-Global so that the space is present as a form of support for commercial expression with the potential for community collaboration space.